Analysis of Precipitation and Precipitable Water Vapor over Iraq for the Period 1948-2011 - Ibrahim, Roaa (Iraqi Journal of Science, 2024)
The water vapor is one of the constituent elements of the rain and the superiorityof its importance in the study of climate because it is the basis on which depends allthe different aspects of condensation. The purpose of research is to analyze the timeseries of the Baghdad station andan analyze these series to see whether there is arelationship between these two variables. Obtained the data used in this researchfrom the National Center for Environmental Prediction for the period from 1948 to2011. The use of statistical criteria included linear regression and Mann Kandal testto find the link. The results of time series monthly presence decrease in rainfall andall months except October, either the results of time series of monthly amount of